Normothermic Cardiopulmonary Bypass in Patient With Waldenström's Macroglobulinemia and Cryoglobulinemia: A Case Report. Issue 6 (15th September 2017) - Satomi, Shiho; Kasai, Asuka; Hamaguchi, Eisuke; Tsutsumi, Yasuo M.; Tanaka, Katsuya
Abstract : Waldenström's macroglobulinemia (WM) manifests as hyperviscosity syndrome. Cryoglobulinemia, which may increase blood viscosity or induce thrombosis in association with decreased body temperature, can occur in combination with WM. We describe the management of an 82-year-old woman with WM, hyperviscosity syndrome, and cryoglobulinemia who required open aortic valve replacement. Decreased body temperature in this patient was prevented during cardiopulmonary bypass by using a forced air warming system and normothermic cardioplegia with continuous warm blood cardioplegia perfusion.